Identify Stressful Factors Causing Dissatisfaction In Pre-Hospital Emergency Personnel In Kerman - Farzaneh Mahmoudi Meymand; Mahmoud Nekouei Moghadam; Amin saberi Nia (Tehran University of Medical Sciences, 2013)
Background and Aim: The Emergency Medical services(EMS) is a community-based health management system that has coordinated with the entire health care system and the employees are the most important asset of it. The purpose of this study was to identify the stressful factors that cause dissatisfaction of employee in the pre-hospital EMS in Kerman. Materials and Methods: This study was a qualitative study and sampling was targeted. Acception criteria for the study was more than three years of experience as a technician operating in urban and road sites in the EMS. In this study, semi-structured interviews were conducted with 15 personnels and data was analyzed using "frame structured analysis" was used. Results: This study identified four main axis and fifteen sub axis. The main issues related to the tensions and dissatisfaction include the employees personal problems, organizational problems, poor coordination, and problems with the community. Conclusion: Considering Psychotherapy for staff and the creation of job rotation between the bases are the constructive suggestions for improving employee performance and improve the system of EMS is Kerman.